Analysis of 4 Single-Nucleotide Polymorphisms in Relation to Cervical Dysplasia and Cancer Development Using a High-Throughput Ligation-Detection Reaction Procedure. Issue 9 (1st November 2011) - von Keyserling, Helmut; Bergmann, Thomas; Schuetz, Miriam; Schiller, Ursula; Stanke, Jonas; Hoffmann, Corinna; Schneider, Achim; Lehrach, Hans; Dahl, Andreas; Kaufmann, Andreas M.
Abstract : Background: Host genetic characteristics and environmental factors may correlate with risk for cervical cancer development. Here we describe a retrospective screening study for single nucleotide polymorphisms (SNPs) in genetic markers TP53, MTHFR, CYP1A1, and CYP2E1 in 749 patients. Methods: A multiplex ligation-dependent polymerase chain reaction approach was applied. We used archived material from human papillomavirus tests and correlated SNP genotypes to the corresponding clinical data. Semantic integration was used to identify and evaluate the clinical status from electronic health records. Results: An association with cervical cancer and high-grade dysplasia was found for the rare homozygous CC genotype (rs4646903) in CYP1A1 (odds ratio [OR], 8.862). Odds ratios were also significantly elevated for heterozygous MTHFR CT genotype (rs1801133; OR, 1.457). No significant association was found in TP53 (rs1042522) and CYP2E1 (rs3813867). In addition, we found smokers at higher risk (OR, 2.688) and identified pregnancies as a significant risk factor (OR, 1.54). Conclusions: Our protocol enables a feasible way for further retrospective large sample size evaluation of potential genetic markers. This study revealed genetic associations of a rare SNP genotype with cervical dysplasia in one of the largest patient sample to date that warrants further investigation.